Changes in the Content of Dietary Fiber, Flavonoids, and Phenolic Acids in the Morphological Parts of Fagopyrum tataricum (L.) Gaertn Under Drought Stress - Krzysztof Dziedzic; Pathumi Ariyarathna; Artur Szwengiel; Marzanna Hęś; Karolina Ratajczak; Danuta Górecka; Hanna Sulewska; Jarosław Walkowiak (Molecules)
Background: Tartary buckwheat is a plant recognized for its resistance to various environmental stresses. Due to its valuable source of phenolic compounds, Fagopyrum tataricum is also characterized as a medicinal plant; therefore, the aim of this study was to investigate the drought stress for the levels of phenolic compounds in the morphological parts of the plant. Methods: This experiment was conducted in 7 L pots under laboratory conditions. Phenolic compounds were identified using a UHPLC–MS chromatography system. Antioxidant activity was assessed using well-known methods, including the DPPH scavenging activity and ferrous ion chelating activity. Results: In Tartary buckwheat leaves, stems, seeds, and husks, 57 phenolic compounds were identified, with a predominance of quercetin 3-rutinoside, quercetin, kaempferol-3-rutinoside, kaempferol, and derivatives of coumaric acid. It was observed that the Tartary buckwheat samples subjected to drought stress exhibited a slight decrease in the majority of individual phenolic compounds. Conclusions: The measurement of biological parameters indicated that plant regeneration after drought stress demonstrated a rapid recovery, which can be a positive response to the progression of climate changes.